Dynamic Modeling and Simulation of Control System for Pneumatic Servo Valve Using Piezoelectric Actuator - Beni, Mohsen Heydari; Homaei, Hadi; Kiani, Ehsan; Abbaspour, Fatemeh (Ciência e Natura, 2015)
In this study design and simulation of controller for piezoelectric pneumatic servo valve is done. The dynamic model of the valve using analytical approach and the working principle of the servo valve is analyzed. The pole placement method is used to design a controller using observed variables. The valve controls the situation and position of actuator. Then for the system, full order state observer and PID controller based on ITAE (Integral Time Absolute Error) criteria are investigated and the response of system with these controllers is shown and a comparison is done for different schemes of controller design and the best design is selected for the system.